Massiv-parallele und großskalige Phasenfeldsimulationen zur Untersuchung der Mikrostrukturentwicklung - Hötzer, Johannes (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2017)
The development of tailored materials with defined properties requires a deep understanding of the microstructure evolution. In the first part, the microstructure evolution during the directional solidification of ternary eutectics with a highly optimized phase-field solver in the waLBerla-framework is studied. In the second part, the microstructure evolution under the influence of pores at the grain boundaries in the final sintering stage is analyzed with the PACE3D solver.